Inhibition of Glucose-6-Phosphate Dehydrogenase Reverses Cisplatin Resistance in Lung Cancer Cells via the Redox System - Hong, Weipeng; Cai, Peiheng; Xu, Chuncao; Cao, Di; Yu, Weibang; Zhao, Zhongxiang; Huang, Min; Jin, Jing (Frontiers in Pharmacology, 2018)
The pentose phosphate pathway (PPP), which branches from glycolysis, is correlated with cancer cell proliferation, survival and senescence. In this study, differences in the metabolic profile of the PPP and the redox status of human lung carcinoma A549 cells and cisplatin-induced multidrug-resistant A549/DDP cells were analyzed and evaluated. The results showed that A549/DDP cells exhibited differential PPP-derived metabolic features and redox-related molecules. A549/DDP cells exhibited increased expression and enzymatic activity of PPP enzyme glucose-6-phosphate dehydrogenase (G6PD). Furthermore, as demonstrated by the apoptotic rate, cell viability, and colony formation, inhibition of G6PD by siRNA or an inhibitor sensitized A549/DDP cells to cisplatin. Additionally, inhibition of G6PD restored the cisplatin sensitivity of A549/DDP cells by influencing redox homeostasis. In conclusion, overcoming cisplatin resistance through inhibition of G6PD could improve the understanding of the mechanisms underlying cisplatin-induced resistance in human lung cancer and may provide insights into the therapeutic potential of this treatment to combat resistance.